Klasifikasi Rumput Liar Menggunakan Deep Learning Dengan Dense Convolutional Neural Network - Yusril Nurhadi AS; Dadang Iskandar Mulyana; Yuma Akbar (STMIK Banjarbaru, 2023)
Weed control research using robots increases productivity in agriculture. Most of the work focused on developing robotics for farmland, ignoring the weed management issues facing pasture farmers. In developing a weed control robot, it takes a lot of hardware and software components and devices. In software requirements, there is a need for a system that can help the robot to recognize weeds that it will take care of for land management. The biggest obstacle to the expansion of robotic weed control is the robust classification of weed species in their natural environment. This work contributes to the method of classifying weed species using Deep Learning with Dense Convolutional Neural Network. The wild grass images used are Chinee apple, Snake weed, Lantana, Prickly acacia, Siam weed, Parthenium, Rubber vine and Parkinsonia. This image recognition implementation is done by using Resnet50 on Tensorflow at Google Collaboratory. The dataset used in the test is the DeepWeeds dataset which consists of 17,509 images labeled with 10,505 training data and 3,502 test data used to produce evaluation values with 78% precision, 78% recall, 78% f1-score, 77.73% accuracy and loss. 0.6676.Kata kunci: ResNet50; Convolutional Neural Network; Image Classification.AbstrakPenelitian kontrol gulma menggunakan robot meningkatkan produktivitas di bidang agrikultur. Sebagian besar pekerjaan fokus pada pengembangan robotika untuk lahan pertanian, mengabaikan masalah pengelolaan gulma yang dihadapi peternak padang rumput. Dalam mengembangkan robot pengendali gulma dibutuhkan banyak perangkat dan komponen hardware maupun software. Pada kebutuhan software perlu adanya sistem yang dapat membantu robot untuk mengenali tanaman gulma yang akan diurusnya untuk pengelolaan lahan. Kendala terbesar untuk peluasan pengendalian gulma dengan robot adalah klasifikasi kuat species gulma di lingkungan alami mereka. Karya ini berkontribusi pada metode pengklasifikasian species gulma menggunakan Deep Learning dengan Dense Convolutional Neural Network. Citra tanaman rumput liar yang digunakan adalah Chinee apple, Snake weed, Lantana, Prickly acacia, Siam weed, Parthenium, Rubber vine dan Parkinsonia. Implementasi pengenalan citra ini dilakukan dengan memanfaatkan Resnet50 pada Tensorflow di Google Collaboratory. Dataset yang digunakan dalam pengujian adalah dataset DeepWeeds yang terdiri dari 17.509 gambar berlabel sebanyak 10.505 data training dan 3.502 data test yang digunakan menghasilkan nilai evaluasi dengan nilai precision 78%, recall 78%, f1-score 78%, akurasi 77,73% dan loss 0.6676.Kata kunci: ResNet50; Convolutional Neural Network; Image Classification.